1727. Sustained Antimicrobial Activity of a Novel Disinfectant Against Healthcare Pathogens. (26th November 2018) - Rutala, William; Gergen, Maria; Sickbert-Bennett, Emily; Anderson, Deverick J; Weber, David
Abstract: Background: Environmental contamination plays an important role in the transmission of MRSA, VRE, and C. difficile . Suboptimal compliance with hand hygiene or inappropriate glove use can result in indirect transfer of these pathogens to patients. This study evaluates a novel disinfectant that claims to kill microbes on surfaces for ≥24 hours. Methods: We investigated the persistent antimicrobial activity of a novel disinfectant using an EPA protocol for sustained disinfecting activity. In brief, surfaces are inoculated, treated with the novel disinfectant, allowed to dry, and then abraded using a standardized abrasion machine under multiple alternating wet and dry wipe conditions ( N = 12) interspersed with 6 re-inoculations. After 24 hours, the surface was re-inoculated a final time and ability of the disinfectant to kill ≥99.9% of 9 test microbes within 5 minutes was measured on 3 test surfaces (glass, formica, and stainless steel). Results: The novel disinfectant demonstrated a 3–5 log10 reduction in 5 minutes when testing S. aureus, VRE, C. auris, CRE E. coli and antibiotic-sensitive strains of E. coli, and Enterobacter sp. (table). The disinfectant demonstrated lower killing for CRE isolates of Enterobacter sp. and K. pneumoniae, and for antibiotic-sensitive K. pneumoniae ( 2 log10 reduction in 5 minutes). When the novel disinfectant was compared with 3 other commonly used disinfectants using the same methodology with S. aureus, the mean log10 reductions were: 4.4 (novel disinfectant); 0.9 (quat-alcohol); 0.2 (improved hydrogen peroxide); and 0.1 (chlorine). Conclusion: Persistent disinfectants may reduce or eliminate the problem of recontamination and minimize the role of environmental surfaces in transmission of healthcare pathogens. Disclosures: W. Rutala, PDI: Consultant and Speaker's Bureau, Consulting fee and Speaker honorarium. D. Weber, PDI: Consultant, Consulting fee